Sie sind auf Seite 1von 13

SUMMARY OF CHAPTER 2

2.1 FUNCTIONS

a. A function assigns each input number to one output number.


b. The set of all input numbers is the domain of the function.
c. The set of all output numbers is the range.

A function f : X →Y s a rule that assigns, to each element x of X, at


i
most one element of Y. If an element is assigned to x in X, it is
denoted by f(x). The subset of X consisting of all the x for which f(x)
is defined is called the domain of f. The set of all elements in Y of the
form f(x), for some x in X, is called the range of f.

d. Not all equations in x and y define y as a function of x.


e. Some equations in two variables define either variable as a function of the
other variable.
f. The letters f, g, h, F, G, and so on are used to name functions.

f(x), which is read “f of x”, and which means the output, input
In the range of f, that results when the rule f is applied to
the input x, from the domain of f.
f(x)

output

g. The output f(x) is the same as y. But since y=x+2, we can write f(x)=x+2.
h. Outputs are also called function values.
 The equation g(x)=x3+x2
Equality of functions

To say that two functions f , g : X → Y are equal, denoted f = g, is to say that


1. The domain of f is equal to the domain of g;
2. For every x in the domain of f and g , f(x) = g(x).
Example 1: Determining Equality of Functions
( x  2)( x  1)
a. f ( x) 
( x  1)

b. g ( x)  x  2

Example 2: Finding Domains

x
a. f ( x)  2
x x2
Solution: x2 - x 2 =0
(x-2)(x+1)=0
X =2, -1

b. g (t )  2t  1

Example 3: Finding Domain and Function Values


Let g(x)=3x2 - x + 5. Any real number can be used for x, so the domain of g is all
real number.

a. Find g(z)

Solution: g(z)=3(z)2 - z +5
=3r2 - z +5
b. Find g(r2)

Solution: g(r2)=3(r2)2 _ r2 +5
= 3r4-r2+5
c. Find g(x+h)

Solution: g(x+h) =3(x+h)2 - (x+h)+5


=3(x2+2hx+h2) - x - h+5
=3x+6hx+3h - x - h+5
Example 4: Finding a Difference Quotient
f ( x  h)  f ( x )
If f(x)=x2, find .
h
Solution: f(x+h)-f(x) = (x+h)2 - x2
h h
= x2+2hx+h2 - x2 = 2hx+h2
h h

= h(2x+h)
h
= 2x+h for h ≠ 0
2.2 COMBINATIONS OF FUNCTIONS

 There are several ways of combining two functions to create new function.
Suppose f and g are the functions given by

f (x) = x2 OR g (x) = 3x

 By adding f (x) + g (x) gives

f (x) + g (x) = x2 + 3x

 This operation called the sum of f and g, denoted f + g. Its function value at
x is f (x) + g (x). It is

(f + g) (x) = f (x) + g (x)

= x2 + 3x

 For example, put x = 2

(f + g) (2) = f (x) + g (x)

= (2)2 + 3 (2)

= 10
 In general, for any functions f.g : X (-∞,∞) The Sum will be ( f + g ) ,
The Difference will be ( f – g ) , the Product ( f . g ) and the Quotient ( f / g )
as follows:

 ( f + g) ( x ) = f ( x ) + g ( x )

 (f–g)(x) = f(x)–g(x)

 ( f.g ) ( x ) = f(x).g(x)

 f / g (x) = f(x)/g(x)

Example - Combination of Functions

If f(x) = 3x – 1 and g(x) = x2 + 3x , find

a) ( f + g ) ( x )

b) ( f – g ) ( x )

c) ( f.g ) ( x )

d) f (x)
g

e) ( 1 f ) ( x )
2
Solution:

a) f ( x ) + g ( x ) = ( 3x - 1 ) + ( x2 + 3x )

= x2 + 6x – 1

b) f ( x ) – g ( x ) = ( 3x – 1 ) – ( x2 + 3x )

= - 1 – x2 or

= x2 + 1

c) f ( x ) . g ( x ) = ( 3x – 1)( x2 + 3x )

= 3x3 + 8x2 - 3x

d) f ( x ) = ( 3x – 1 )

g(x) x2 + 3x

e) 1 ( f ( x ) ) = 1 ( 3x-1 )

2 2

= ( 3x – 1 )

2
 We can also combine two functions by first applying one function to
an input and then applying the other function to the output of the
first.

 This is called composition.

2.3 Composition Of Functions

(f o g) (x) = f (g(x))

(g o f) (x) = g (f(x))

(f o f) (x) = f (f(x))

(g o g) (x) = g (g(x))

Example 1
If f(x) = 2x and g(x) = x + 3, find
a. (f o g) (x)
b. (g o f) (x)
c. g(g(x))

Solution
a. (f o g) (x) = f(g(x))
= f(x + 3)
= 2(x + 3)
= 2x + 6

b. (g o f) (x) = g(f(x))
= g(2x)
= 2x + 3

c. (g o g ) (x) = g(g(x))
= g(x +3)
=x+3+3
=x+6

Example 2

If f(x) =3x and g(x) = x + 4, find


a. (f o g) (x)
b. (g o f) (x)

Solution
a. (f o g) (x) = f(g(x))
= f(x + 4)
= 3(x + 4)
= 3x + 12

b. (g o f) (x) = g(f(x))
= g (3x)
= 3x + 4
Example 3

If + 4 x – 3 and g(x) = 2x + 1, find


a. f(g(x))
b. g(f(1))
c. (g o g) (x)

Solution
a. f(g(x)) = f(2x + 1)
= (2x+1)2 + 4 (2x + 1) – 3
= (2x + 1) (2x + 1) + 4 (2x + 1) – 3
= 4x2 + 2x + 2x + 1 + 8x + 4 – 3
= 4x2+ 12x + 2

b. g(f(1)) = g [12 + 4 (1) – 3 ]


= g (2)
= 2 (2) + 1
=5

c. (g o g) (x) = g(g(x))
= g(2x + 1)
= 4x + 2 + 1
= 4x + 3
Problem solving

Question 45

x
2x=5

X=

Question 46
=3

+1=
+ =
=
=
2x = 3

X=

X= , x=1
Question 47

x (x+2)=3

X=

X=

X= , x=
X=1 , x=-3

Question 48

=8

X= 2
Reference

Richard S. Paul / Richard J. Wood / Richard J. Wood . Introductory Mathematical


Analysis 14 Edition, April 2018.

The American Heritage @ Science Dictionary. 2011. Meaning of Functions. From


https://www.dictionary.com/browse/function
APPENDIX

Das könnte Ihnen auch gefallen